2023
DOI: 10.1038/s41598-023-28259-y
|View full text |Cite
|
Sign up to set email alerts
|

Predicting severity in COVID-19 disease using sepsis blood gene expression signatures

Abstract: Severely-afflicted COVID-19 patients can exhibit disease manifestations representative of sepsis, including acute respiratory distress syndrome and multiple organ failure. We hypothesized that diagnostic tools used in managing all-cause sepsis, such as clinical criteria, biomarkers, and gene expression signatures, should extend to COVID-19 patients. Here we analyzed the whole blood transcriptome of 124 early (1–5 days post-hospital admission) and late (6–20 days post-admission) sampled patients with confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 56 publications
(83 reference statements)
0
15
0
Order By: Relevance
“…A similarly- sized study of 124 participants with samples collected at two time points, 1-5 days post hospital admission and 6-20 days post admission, found upregulation of several pathways in those with severe COVID-19 disease. These pathways included neutrophil degranulation, interferon α/β/γ signalling, IL-4 and IL-13 signalling, oxidative stress and TNF-α signalling via NFκ-B a ( 48 ). They also compared the timing of sampling with disease outcome and although gene expression trajectories change over two time points taken, they found that the signatures were still significantly dysregulated between severe versus moderate COVID-19 and between those who died and those who survived.…”
Section: Discussionmentioning
confidence: 99%
“…A similarly- sized study of 124 participants with samples collected at two time points, 1-5 days post hospital admission and 6-20 days post admission, found upregulation of several pathways in those with severe COVID-19 disease. These pathways included neutrophil degranulation, interferon α/β/γ signalling, IL-4 and IL-13 signalling, oxidative stress and TNF-α signalling via NFκ-B a ( 48 ). They also compared the timing of sampling with disease outcome and although gene expression trajectories change over two time points taken, they found that the signatures were still significantly dysregulated between severe versus moderate COVID-19 and between those who died and those who survived.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, long-term outcomes of both sepsis (post-sepsis syndrome) and COVID-19 (“long COVID”) share multiple neurocognitive and immune deficits ( 13 , 14 ). In addition, we recently showed that endotypes identified in a cohort of all-cause sepsis patients could also predict severity in COVID-19 patients, indicating further parallels in pathophysiology between the two diseases ( 15 , 16 ). Compared to other viral diseases such as influenza, COVID-19 generally has higher TNFα/IL-1β-associated inflammation ( 17 ) and lower interferon responses ( 18 ).…”
Section: Introductionmentioning
confidence: 90%
“…A number of investigators have applied whole blood transcriptomics to identify predictive scores for deterioration in COVID-19 (20,(22)(23)(24)(25)(26). We did not attempt this in our cohort as the number of COVID-19 patient RNA samples that successfully underwent RNA-seq was relatively small (n=88) and all stemmed from the first (Wuhan) wave of COVID-19, prior to specific treatments being available, with limited access to intensive care or non-invasive ventilation, and at a time when inpatient mortality was very high, just under 30%.…”
Section: Discussionmentioning
confidence: 99%